A concept of the transition radiation detector for a hadron separation in a forward direction of the LHC experiments. (December 2020) - Belyaev, N; Cherry, M L; Doronin, S A; Filippov, K; Fusco, P; Gargano, F; Konovalov, S; Loparco, F; Mazziotta, M N; Mufazalova, A; Nechaeva, S; Ponomarenko, D; et al.
Abstract: Studying of hadron production in forward direction at the LHC energy has a great interest both for understanding of the fundamental QCD processes and also in applied areas such as the description of ultra-high energy cosmic particle interactions. The energies of secondary hadrons in such studies almost reach the maximum energy available at the LHC of ~6 TeV, which corresponds to a Lorentz γ -factor up to 10 4 and above. The only effective technique able to identify particles in this range is based on the transition radiation detectors (TRD). Prototypes of such kind of detector were built and tested at the CERN SPS accelerator. Some experimental results obtained in these tests are briefly presented here and compared with Monte Carlo (MC) simulations. MC model demonstrates a good agreement with the experiment. On this basis a concept of a full-scale TRD optimized for the hadron identification in the TeV energy region is proposed. Different particle identification techniques were considered and examined. The expected detector performance to reconstruct secondary hadrons produced in forward direction at the LHC is presented.